1984
DOI: 10.1038/bjc.1984.209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumour age response to radiation for cells derived from tissue culture or solid tumours

Abstract: Summary Direct comparison of the cell age response of 9L and KHT tumour cells derived either from tissue culture or solid tumours was achieved. Cells from dissociated KHT and 9L tumours (the latter implanted either subcutaneously or intracerebrally) and cells from tissue culture were separated into homogenous sized populations by centrifugal elutriation. In both tumour models these homogeneous sized populations correspond to populations enriched at different stages of the cell cycle. The survival of these elut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In general cellular radiation resistance increases during S phase and reaches maximum in the latter part of S phase (Pawlik & Keyomarsi 2004), however, Keng et al (1984) reported that in KHT-C cells the late G1 population was slightly less radiosensitive than cells from other cell cycle stages, therefore hypoxia-induced enrichment of the G1 population might be a reason for increased radiation resistance in hypoxic KHT-C cells. However, our data in Figure 3 indicated that enrichment of the G1 population by Table I.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In general cellular radiation resistance increases during S phase and reaches maximum in the latter part of S phase (Pawlik & Keyomarsi 2004), however, Keng et al (1984) reported that in KHT-C cells the late G1 population was slightly less radiosensitive than cells from other cell cycle stages, therefore hypoxia-induced enrichment of the G1 population might be a reason for increased radiation resistance in hypoxic KHT-C cells. However, our data in Figure 3 indicated that enrichment of the G1 population by Table I.…”
Section: Discussionmentioning
confidence: 95%
“…This is confirmed in all of the three tumor cell lines being used for this study, in which we observed the enrichment of the G1 population after hypoxia treatment ( Figure 3A). Although late S phase cells are generally considered as the least radiosensitive cell population (Pawlik & Keyomarsi 2004), it has also been reported that in KHT-C cells late G1 population is the least radiosensitive (Keng et al 1984).…”
Section: Hypoxia-induced Cell Cycle Arrest and Its Effect On Radiosenmentioning
confidence: 99%
“…This is because in the KHT sarcoma, there is little difference between the radiation sensitivity of the most resistant S and G1 cell subpopulations Keng et al, 1984) i.e., the cell subpopulations which dominate the dimmest and brightest sort fractions. However, when Hoechst 33342 sorting is used to study hypoxic subpopulations in other tumour models, differences in the cell cycle distributions in the sorted fractions may need to be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 96%
“…There have been many eloquent studies of the radiation dose-response relationship (“dose-response”) of lung tissue aimed to better understand the underlying radiobiology 2 and to model 24 the radiation delivery effects of regional dose magnitude, dose rate, dose volume, fractionation schedule, and type of radiation, 25 among others. Historically, these studies measured rates of cell 26 or animal death 27 and, more recently, have focused on subclinical changes in pixel-wise density observed with chest CT. 28 While analysis of dose-response has important clinical implications, here we sought to answer whether PT is safer (causes less overall lung tissue damage) than photon therapy, given the differences in the underlying radiobiology and modern radiation delivery for each modality. For this objective, total tissue reaction is the more relevant metric.…”
Section: Discussionmentioning
confidence: 99%